If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10y = -20findx Solving 5x + 10y = -20dfinx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20dfinx' to each side of the equation. 5x + 20dfinx + 10y = -20dfinx + 20dfinx Reorder the terms: 20dfinx + 5x + 10y = -20dfinx + 20dfinx Combine like terms: -20dfinx + 20dfinx = 0 20dfinx + 5x + 10y = 0 Add '-10y' to each side of the equation. 20dfinx + 5x + 10y + -10y = 0 + -10y Combine like terms: 10y + -10y = 0 20dfinx + 5x + 0 = 0 + -10y 20dfinx + 5x = 0 + -10y Remove the zero: 20dfinx + 5x = -10y Combine like terms: -10y + 10y = 0 20dfinx + 5x + 10y = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(4dfinx + x + 2y) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(4dfinx + x + 2y)' equal to zero and attempt to solve: Simplifying 4dfinx + x + 2y = 0 Solving 4dfinx + x + 2y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 4dfinx + x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 4dfinx + x + 0 = 0 + -2y 4dfinx + x = 0 + -2y Remove the zero: 4dfinx + x = -2y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x=56-3x | | 3t+4+t=6 | | 25-2x=-(-6+7) | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | x=56-3x | | 6w-5= | | 0.4x=2.40 | | 2(4y-4)-6=17+y | | 3t+4+t=6 | | 2(4y-4)-6=17+y | | 6w-5= | | 25-2x=-(-6+7) | | 25-2x=-(-6+7) | | 6w-5= | | -2/3[24t-27]=-8[-t-4]-6 | | M/5/6=24 | | 9asd+10=21asd | | 3(k-8)-1(k+5)=23 | | 9asd+10=21asd | | 8m-15=77-3m | | 4x++12-4+2x= | | (5u+8)(6-u)=0 | | -57=6x+x-1 | | 4(.50+.75y)+3y=4 | | h(t)=-16t^2+72t+24 | | 5y-3(y-1)=4y+2 | | 7x+11x-8+x+12=180 |